Kebijakan Program PPG dalam Mewujudkan Sustainable Development Goals (SDGs) dan Meningkatkan Mutu Profesionalisme Guru - Permatasari, Nanda Santin (Universitas Negeri Malang, 2024)
Abstract This article aims to examine the role of the PPG policy in realizing the Sustainable Development Goals (SDGs) and improving the quality of teacher professionalism. PPG is an educational program organized to prepare educational and non-educational undergraduate graduates to master the competencies of teachers as a whole in accordance with educational standards. Educator certificates can be obtained through professional training programs or Professional Teacher Education (PPG). In accordance with the SDGs, PPG is considered a key driver for building sustainable education through curriculum and teaching practices. The method in this article uses library research. Library study can be defined as a series of activities related to library data collection methods, reading and recording and processing research materials. The result of this study is that in the context of achieving the Sustainable Development Goals (SDGs), PPG has a strategic role in improving the quality of teacher professionalism. The SDGs emphasize the importance of quality education and universal access to education. Through PPG, concrete steps can be taken to improve teachers' qualifications and competencies, and reduce disparities in access to education in various regions. Effective implementation of the PPG policy requires collaboration between the government, educational institutions and communities, and the integration of sustainable development principles in education. Thus, PPG has great potential to become a major force in achieving the SDGs and shaping a more educated, sustainable and inclusive society.